Disminorrea primaria en las adolescentes de los colegios del Área Urbana de la ciudad de Zumba, cantón Chinchipe, provincia de Zamora Chinchipe. - Velásquez Jiménez, Cecilia Maribel (2016)
Dysmenorrhea is painful menstruation and as the most frequently reported menstrual disorder and one of the most frequent chronic pelvic processes suffered by women of reproductive age, it becomes important to obtain data from unseen populations. PRIMARY DISMENORRHEA IN THE ADOLESCENTS OF THE SCHOOLS OF THE URBAN AREA OF THE CITY OF ZUMBA, CANTON CHINCHIPE, PROVINCE OF ZAMORA CHINCHIPE, given the breadth of the subject this research was carried out with a descriptive and transversal study in the urban area of the city of Zumba Canton Chinchipe Province of Zamora Chinchipe in two schools in the city of Zumba, the Educational Unit "Manuela Sáenz" and the Educational Unit "Zumba" we find a total of 355 adolescents between 10 and 20 years old living in the city of Zumba and Of nearby places from which a sample of 296 were taken that met the inclusion criteria to which they were applied a survey from where the data was obtained. This research determined the prevalence of this disease, the main clinical features of dysmenorrhea pain, the most used therapeutic measures and the effects of it is on academic assistance of adolescents. Among the results we highlight that: The prevalence of primary dysmenorrhea is 79%. The age of the first menstruation is between 12 and 13 years and with a duration of 4 to 5 days with 44%. The intensity of the pain is moderate in 52%, accompanied by abdominal distension in 89%. Among the pharmacological measures, NSAIDs (57%), non-pharmacological drugs (42%) and Found a 56% percentage of academic absenteeism due to primary dysmenorrhoea. KEYWORDS: Dysmenorrhea, pain, adolescence